Plot Sebagai Penjelasan Sejarah: Perihal Kembalinya Arjuna dari Kematian atau Hilangnya - Sri Kuncoro; G.R. Lono Lastoro Simatupang; Timbul Haryono (Universitas Gadjah Mada, 2019)
Arjuna died. He was accidentally killed by Prabu Suteja. There was a war between Prabu Suteja and Raden Purwagada, sons of Prabu Kresna. In its next few scenes, Arjuna is revived and appears in Dwarawati Kingdom’s scene without any explanation. It is narrated in a play entitled Kresna Adu Jago by Ki H. Anom Rusdi from Cirebon. Arjuna disappeared since the war between Prabu Kresna and Dewi Pertiwi’s son Bomanerakasura and Samba the son of Prabu Kresna and Dewi Jembawati. Punakawan reported that Arjuna had died in the war. Arjuna and punakawan were both vanished while Arjuna actually lives as an ascetic in Mintaraga cave and later be called as Begawan Ciptaning Mintaraga. Arjuna as Begawan Ciptaning Mintaraga appears in Mintaraga play by Ki Timbul Hadiprayitno from Yogyakarta. Kresna Adu Jago and Mintaraga plays are not identical. Names of the involved characters are different though problems within both plays are similar: a war between sons of Kresna which exacerbates the next problem. The next problem in Kresna Adu Jago is Nerakasura’s grudge against the death of his father, Prabu Suteja, which makes him face Gatutkaca and meet the same fate: died in Gatutkaca’s hands. Problem in Mintaraga is liberation efforts of Dewi Supraba in avoiding Prabu Nirbita Niwatakaca’s intention to marry the angel. Both plays appear identical only on matters of Arjuna’s death, disappearance, as well as his reappearance. Arjuna’s reappearance have the most important difference: Arjuna’s reappearance in Kresna Adu Jago is without reason while it has reasons in Mintaraga. In theories of plot, this cause-effect or effect-cause patterns (instead of a time-based sequence) are called plot. In historical theories, this cause-effect interaction, rather than a sequence of events based on the background of time, is referred to as historical explanation. Through theories of plot, Arjuna’s death in Kresna Adu Jago is a muted history. Through historical theories, Arjuna’s reappearance in Mintaraga is a forged history. Both ways of telling, as options of storytelling, are equally valuable as aesthetic strategies.